AN EXPERIMENTAL STUDY OF PHASE EQUILIBRIA IN THE SYSTEM H2O-CO2-NACL AT 800°C AND 9 KBAR - Shmulovich K.I.; Graham C.M. (My University, 1999)
Phase equilibria in the ternary system H2O-CO2-NaCl were studied at 800°C and 9kbar in internally heated gas pressure vessels using a modified synthetic fluid inclusion technique. The low rate of quartz overgrowth along the `b' and `a' axes of quartz crystals was used to avoid fluid inclusion formation during heating, prior to attainment of equilibrium run conditions. The density of CO2 in the synthetic fluid inclusions was calibrated using inclusions in the binary H2O-CO2 system synthesised by the same method and measured on the same heating-freezing stage. In the two-phase field, two types of fluid inclusions with different densities of CO2 were observed. Using mass balance calculations, these inclusions are used to constrain the miscibility gap and the orientation of two-phase tie-lines in the H2O-CO2-NaCl system at 800 °C and 9 kbar. The equation of state of Duan et al. (1995) approximately describes the P-T section of the ternary system up to about 40wt% of NaCl. At higher NaCl concentrations the measured solubility of CO2 in the brine is much smaller than predicted by the EOS. A “salting out” effect must be added to the equation of state to include coulomb interaction in the model of Anderko and Pitzer (1993) and Pitzer and Jiang (1996). The new experimental data together with published data up to 5kbar (Shmulovich et.al. 1995) encompass practically all subsolidus crustal P-T conditions. A feature of the new experimental results is the large compositional range in the H2O-CO2-NaCl system occupied by the stability fields of halite+CO2-rich fluid±H2O-NaCl brine. The prediction of halite stability in equilibrium with CO2-rich fluid in deep-crustal rocks is supported by recent petrological and fluid inclusion studies of granulites.